STATE ADMINISTRATIVE LAW IN THE IMPLEMENTATION OF PUBLIC SERVICES RELATED TO HUMAN RIGHTS - Melky Suhery Simamora; Azmiati Zuliah (Universitas Dharmawangsa Medan, 2021)
The object of administrative law is government power (bestuur; Verwaltung). State Administrative Law in the implementation of public services, the government often uses authority not by what is regulated in the law it violates human rights. Therefore, on the other hand, the function of state administrative law in creating good and authoritative governance is needed, including normative functions, instrumental functions, and legal guarantee functions, all three of which are part of the implementation to create a clean government, by the principles of state law. About the concept of good governance, state administrative law functions to protect human rights. The government carries out activities by applicable regulations or based on the principle of legality so that it will not lead to inappropriate service behavior which is an administrative mall act that is detrimental to people who want to obtain public services. This paper wants to analyze the correlation between state administrative law and human rights, aiming to see how the function of public services to implement good governance is good governance and forms of violations of public administration which are forms of human rights violations in the implementation of public services. The research method uses a normative juridical approach. This study concludes that efforts to implement good governance will be carried out if good governance can be implemented properly as well. Good governance will be born from a clean government, transparency, and accountability and it is undeniable that there are still various human rights violations in the implementation of public administration. It is hoped that this paper can provide input so that the guarantee of services by state administrators to citizens will be guaranteed properly.State Administrative Law, Public Service, Law, and Human Rights